Input clustering and the microscale structure of local circuits - DeBello, William M.; McBride, Thomas J.; Nichols, Grant S.; Pannoni, Katy E.; Sanculi, Daniel; Totten, Douglas J. (Frontiers in Neural Circuits, 2014)
The recent development of powerful tools for high-throughput mapping of synaptic networks promises major advances in understanding brain function. One open question is how circuits integrate and store information. Competing models based on random versus structured connectivity make distinct predictions regarding the dendritic addressing of synaptic inputs. In this article we review recent experimental tests of one of these models, the input clustering hypothesis. Across circuits, brain regions and species, there is growing evidence of a link between synaptic co-activation and dendritic location, although this finding is not universal. The functional implications of input clustering and future challenges are discussed.